Pengetahuan Dan Kefahaman Masyarakat Islam Terhadap Fatwa Dan Amalan Sertu Di Malaysia - Mohd Mahyeddin Mohd Salleh; Irwan Mohd Subri; Ahmad Rafiki; Mas Nooraini Haji Mohiddin; Cecep Soleh Kurniawan (UTM Press, 2026)
Indexed by MyCite